2021
DOI: 10.1177/15353702211061883
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of PPM1A: From structure to disease

Abstract: PPM1A (magnesium-dependent phosphatase 1 A, also known as PP2Cα) is a member of the Ser/Thr protein phosphatase family. Protein phosphatases catalyze the removal of phosphate groups from proteins via hydrolysis, thus opposing the role of protein kinases. The PP2C family is generally considered a negative regulator in the eukaryotic stress response pathway. PPM1A can bind and dephosphorylate various proteins and is therefore involved in the regulation of a wide range of physiological processes. It plays a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…BCI is known to inhibit DUSP1 and DUSP6 [51]. Sanguinarine is known to inhibit PP2C family of Mg2 + /Mn2 + -dependent phosphatases which includes PPM1A, PPM1B, PPM1C, PPM1D, PPM1E and PPM1G [5254]. We found that injection of FK506 significantly reduced numbers of proliferating Sox2 + MGPCs om damaged retinas (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…BCI is known to inhibit DUSP1 and DUSP6 [51]. Sanguinarine is known to inhibit PP2C family of Mg2 + /Mn2 + -dependent phosphatases which includes PPM1A, PPM1B, PPM1C, PPM1D, PPM1E and PPM1G [5254]. We found that injection of FK506 significantly reduced numbers of proliferating Sox2 + MGPCs om damaged retinas (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, PPM1B dephosphorylates IKKβ to terminate TNFα-induced NFkB activation [78], and inhibition of NFkB is known to stimulate the proliferation of MGPCs [35]. Sanguinarine is also known to inhibit PPM1A which is known to deactivate pSMAD2/3 [52, 79]; SMAD3-signaling is known to suppress the formation of MGPCs in the chick retina [29]. Thus, inhibition of PPM1A by sanguinarine might be expected to increase MGPC proliferation by suppressing SMAD3- and NFkB-signaling.…”
Section: Discussionmentioning
confidence: 99%
“…2022a), which may induce global non-specific dephosphorylation effects or compensatory effects in the cell line due to the broad number of pathways influenced by PPM1A activity (Li et al . 2015, 2022; Berton et al . 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…As PPM1A is a phosphatase, this suggests that histone-modifying enzymes may be activated or repressed by dephosphorylation to mediate opening of chromatin upon Mtb infection. The unusually large number of DAR in the PPM1A + cells may be partially a result of artificially high overexpression of PPM1A (Berton et al 2022a), which may induce global non-specific dephosphorylation effects or compensatory effects in the cell line due to the broad number of pathways influenced by PPM1A activity (Li et al 2015(Li et al , 2022Berton et al 2022b). We also observe this phenotype through differences in baseline CA and gene expression, compared to WT cells, (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PPM1A, a metal-dependent protein phosphatase, can modulate cell proliferation, apoptosis, and immune response via dephosphorylation, which is related to the occurrence and development of cancers, autoimmune diseases, and neurodegenerative diseases. 30 We recently identified PPM1A as a promising target for HDT against Mtb 31 and developed a small molecule, SMIP-30, to inhibit PPM1A (IC 50 = 1.19 μM). 32 Encouraged by these promising results, herein, we systematically investigate the structure−activity relationship (SAR) and discover SMIP-031, a more potent inhibitor for PPM1A (IC 50 = 180 nM).…”
Section: ■ Introductionmentioning
confidence: 99%